Miksi asiakkaat pysyvät? – Asiakastyytyväisyys ja asiakaspito toimitilavuokrauksessa - Nolvi, Siiri (2025)
Over the past few years, the commercial real estate market has undergone significant changes, driven especially by the impact of the Covid-19 pandemic. Remote work has become an established way of working and with the changed circumstances, selecting properties and committing to long-term leases has become more challenging for companies. As a result, it is increasingly important for property owners to understand the factors that influence customer satisfaction and retention. While the real estate and leasing sectors have been widely studied, the relationship between customer satisfaction and retention in the commercial real estate industry has received relatively little attention. The aim of this study is to provide an additional perspective on this connection. This study focuses on identifying how customer satisfaction affects customer retention in commercial real estate leasing. The analysis is based on customer satisfaction data collected by a Finnish real estate investment company between 2016 and 2023. The final analysis includes responses from 478 tenant organisations. As part of the research, the respondents were divided into two customer groups: current tenants and those who have ended their lease. By comparing satisfaction levels between these two groups, the study highlights which aspects of the tenant experience are most critical to keeping customers long-term. The findings show clear differences in satisfaction between the two groups, both overall and in ten specific areas, which are presented in detail in this report.